Previous Archaeological Excavations along the 'Ostlänken' Railway Corridor 1965-2012: Gullvagnen - A Mesolithic inland settlement in northern Kolmården - Swedish National Heritage Board, UV Öst (Uppsala University, 2020)
An archaeological investigation of ancient monument RAÄ 85 in Krokek parish, Norrköping Municipality, Östergötland was conducted in October 1992 owing to the reconstruction of road E4 between Böksjö and Länsgränsen.

Gullvagnen (RAÄ 85) is most probably an inland settlement dating to the Mesolithic. During the investigation a number of features were discovered, including scattered stones and finds made of quartz and greenstone.

The ZIP-file contains three shapefiles with information on trenches, ancient monuments, archaeological finds and other data from the archaeological survey, as well as two geo-referenced maps (© Lantmäteriet i2014/00696) of the survey in GeoTIFF-format.

Arkeologisk förundersökning av fornlämning RAÄ 85 i Krokeks socken i Norrköpings kommun, Östergötland genomfördes under oktober 1992 med anledning av ombyggnaden av väg E4, sträckan Böksjö-Länsgränsen.

Gullvagnen (RAÄ 85) är sannolikt en inlandsboplats med mesolitisk datering. Vid förundersökningen framkom ett flertal anläggningar, spridd skärvsten samt ett fyndmaterial där kvarts och grönsten dominerar.

ZIP-filen innehåller data i form av tre shapefiler med information om eventuella schakt, påträffade forn- och kulturlämningar och fynd samt andra metadata från den arkeologiska utredningen, samt två georefererade kartor (© Lantmäteriet i2014/00696) över utredningsområdet i GeoTIFF-format.
Tidigare arkeologiska undersökningar längs Ostlänken-korridoren 1965-2012: Gullvagnen - En mesolitisk inlandsboplats i norra Kolmården
Keywords: finds; fynd; c-datering; c-datering; HISTORY; HISTORIA; Archaeology; Arkeologi